(3cJGH aj GdbWGY GdgfOSjs
(3ChdgG (B:s
(3HYO GdHSedI GdMeO ddg eHdZ GdMbGFb GdNGQLI Yf GdMUQ hHYO abO cJH YdeJ ajeG eVj ef GdReGf cJGHkG LGekG dVHW OYGhj GdTcd GdeYQha HGdbWGY s
(3BNQgG (B:s
(3EdG Cf GdfSHI JYJHQ aj GdbWGY ef MjK gj eDdaI ef MjK gj HSjWI hgPG gh GdZQV s
(3Vef eLehY , JQJjHgG (B: 14s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs